Entomofauna asociada al cultivo de pecan en Tucumán, Argentina - Garat Herrera, María Gabriela; Araujo Griet, Patricio; Chalup, Adriana E.; Carrizo, Beatriz Noemi (Universidad Nacional de La Plata, 2024)
Póster de la presentacion